Unsymmetric Cisplatin-Based Pt(IV) Conjugates Containing a PARP-1 Inhibitor Pharmacophore Tested on Malignant Pleural Mesothelioma Cell Lines - Elisabetta Gabano; Giulia Pinton; Cecilia Balzano; Sara Boumya; Domenico Osella; Laura Moro; Mauro Ravera (Molecules, 2021)
Cisplatin is widely employed as a first-line chemotherapeutic agent for many solid tumors, including malignant pleural mesothelioma (MPM). However, its clinical use is limited by heavy side effects and acquired resistance, the latter being mainly related to enhanced DNA repair. Many clinical trials using combinations of platinum drugs and PARP-1 inhibitors (PARPis) have been carried out, with the hope that such combinations might lead to improved therapeutic efficacy against tumors. Here, the synthesis and efficacy in reducing MPM cell viability of four cisplatin-based Pt(IV) prodrugs containing the PARPi 3-aminobenzamide (3-ABA) fragment are described. The most promising conjugate is more effective than cisplatin or cisplatin/3-ABA combination, administered in equimolar doses, in inhibiting PARP-1 activity and inducing apoptosis in BRCA1/2 wild type MPM cells, grown as monolayer or as multicellular spheroids.